The Effect of Average Years of Schooling, Open Unemployment Rate, and Labor Force Participation Rate on the Poor Population in Central Java Province in 2010-2024 - Ilmi Arifah, Sandrina; Cahyono, Hendry (Jurnal Ilmu Ekonomi JIE, 2025)
The research investigates the effect of Average Length of Schooling, Open Unemployment Rate, and Labour Force Participation Rate on the Poor Population in Central Java Province during the period 2010-2024. The study uses a multiple linear regression model based on time-series data from the Central Statistics Agency. The findings reveal that the Average Length of Schooling variable contributes negatively and significantly to the poor population. Then the Open Unemployment Rate variable contributes positively and significantly to the poor population. On the other hand, the Labour Force Participation Rate variable only has a positive but insignificant impact on the poor population. The necessary policy implication is that there needs to be a strategy that focuses more on increasing access to education and creating jobs to reduce the unemployment rate, rather than simply encouraging more people to enter the workforce.